Analysis of the Influence of Organizational Culture, Job Satisfaction and Work Discipline on Employee Performance of Company: Analisis Pengaruh Budaya Organisasi, Kepuasan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Perusahaan - Nizar Rifqi, Muchammad Wildan; Sumartik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and see the influence of organizational culture, job satisfaction and work discipline simultaneously and partially on employee performance at PT Prima Karya Teknik. And to see which of the organizational culture, job satisfaction and work discipline have the most significant effect on the performance of PT Prima Karya Teknik employees. The method used in this study uses a quantitative approach. The data collection technique was carried out by distributing questionnaires with a Likert scale measurement level, interviews and observations. The population in this study are all employees at PT Prima Karya Teknik, totaling 60 people. The sampling technique is saturated sampling technique, namely taking or determining the sample if all the population is used as a sample. The data obtained from the questionnaire was then processed using SPSS Version 22 software. The data analysis techniques used were validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, f test and coefficient of determination test. Based on the analysis results show that organizational culture, job satisfaction and work discipline have a positive and significant effect both simultaneously and partially on the performance of PT Prima Karya Teknik employees. And the most significant variable on the performance of PT Prima Karya Teknik employees is the organizational culture variable.